Institutional Ownership and Corporate Sustainable Growth: Insights from the Indonesian Banking Sector - Amrie Firmansyah; Nafis Dwi Kartiko (Jurnal Dinamika Akuntansi dan Bisnis)
This study investigated the effect of institutional ownership on corporate sustainable growth, with a particular focus on the moderating roles of firm size and firm age. The sample comprises 45 banks listed on the Indonesia Stock Exchange (IDX) from 2004 to 2021, resulting in 578 firm-year observations. Employing Ordinary Least Squares (OLS) regression, the findings indicate that institutional ownership has a negative effect on sustainable growth. However, firm size and firm age do not significantly moderate this relationship for firms with either above-average or below-average asset levels. Further analysis reveals that institutional ownership negatively affects smaller firms, while its impact on larger firms is statistically insignificant. These results suggest that the relationship between institutional ownership and sustainable growth may vary with firm size, although not in a moderating capacity. The findings imply that, while firm size and firm age do not function as moderators, they remain important contextual factors in understanding the influence of institutional ownership on corporate sustainable growth.